2020
DOI: 10.1186/s12877-019-1321-x
|View full text |Cite
|
Sign up to set email alerts
|

People living in nursing care facilities who are ambulant and fracture their hips: description of usual care and an alternative rehabilitation pathway

Abstract: Background:Little is known about treatment provided to people living in nursing care facilities (NCFs) after hospital admission for hip fracture. In addition, there are no clinical guidelines for rehabilitation and recovery following hip fracture for nursing home residents.Methods: As part of a randomised trial (SACRED trial), which investigated the efficacy of a four week in-reach rehabilitation program, data were collected which described routine care for 240 people living in 76 nursing care facilities in So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Hip fracture rehabilitation. Two studies in Australia [106,107] (intervention given to the same residents in both studies) reported on a geriatric rehabilitation program for residents Synopsis of multidisciplinary healthcare service delivery: specialist and direct patient care. A complex guideline-based intervention reduced agitation and disruption behaviour in residents with dementia.…”
Section: Plos Onementioning
confidence: 99%
“…Hip fracture rehabilitation. Two studies in Australia [106,107] (intervention given to the same residents in both studies) reported on a geriatric rehabilitation program for residents Synopsis of multidisciplinary healthcare service delivery: specialist and direct patient care. A complex guideline-based intervention reduced agitation and disruption behaviour in residents with dementia.…”
Section: Plos Onementioning
confidence: 99%
“…Yet, these patients are often left out from rehabilitation, because they are not recognized as good candidates [7]. Discharge coordination in association with rehabilitation and destination sites are reported barriers for a longer hospital LOS [11]; dementia adds to this process by increasing LOS and hospital charges [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…While about 50% of patients with hip fracture may potentially return to their pre-fracture functional level, patients with dementia suffer worse post-fracture functional impairment [ 8 , 9 ]. Although limited, a few research studies reported the benefit of post-hip fracture rehabilitation in dementia patients [ 7 , 10 , 11 ]. Yet, these patients are often left out from rehabilitation, because they are not recognized as good candidates [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Falls, therefore, have a negative effect not only on patients and guardians but also socially and economically on the community [ 81 ]. Existing studies on rehabilitation treatment for fractures caused by falls [ 82 ], community preventive interventions and connections with long-term care [ 83 ], and multi-disciplinary approaches have been performed in other countries. In contrast, the number of studies on systems, such as the integrated association between related community organizations [ 84 ], is decreasing in South Korea [ 85 ].…”
Section: Discussionmentioning
confidence: 99%